Healthy Eating: Meals Without Cooking - Karla P. Shelnutt (EDIS)
Enjoy a word search for the ingredients in this recipe for southwestern black bean salad. This revised 2-page fact sheet was written by Karla P. Shelnutt and published by the UF Department of Family, Youth and Community Sciences, May 2012.